LARES: latency–reduced neighbour discovery for contagious diseases prevention. (10th June 2014) - Liu, Wei; Li, Hong; Chen, Yongle; Zhu, Hongsong; Sun, Limin
Contagious diseases threat seriously to human health and even more to the whole society. One of the most effective ways to control their spread is to isolate the infected patients and their contacts. But in practice, it is quite challenging to target the contacts. Nowadays, the popularity of smart phones provides an efficient solution to record the contact information. The contact recording problem can be formulated as a low power asynchronous neighbour discovery problem. Traditional neighbour discovery protocols are not suitable for our application, due to their inadequate consideration for high mobility and crowd density–latency relationship. In this paper, we propose LARES, a group based cooperative neighbour discovery protocol. LARES reduces the discovery latency by selecting appropriate phase difference combination to detect neighbours by group. Evaluation results show that LARES can dramatically reduce the discovery latency. When using 10% duty cycle, the expected and the worst case latency are about 1/20 of Disco in single neighbour discovery scenario. The average total latency to discover all the neighbours in an area is only 1/3 of Disco.